Praktek Pemilihan Makanan Kemasan Berdasarkan Tingkat Pengetahuan Tentang Label Produk Makanan Kemasan, Jenis Kelamin, dan Usia Konsumen di Pasar Swalayan ADA Setiabudi Semarang - Vania Chandra Devi; Agus Sartono; Joko Teguh Isworo (Universitas Muhammadiyah Semarang, 2013)
Today, many consumers in Indonesia who do not attention to the selection ofpackaged foods based on food labels are listed in the packaged food. There are several factors that can influence consumer behaviour towards the selection of packaged foods, such as age, income, gender, education, and work status. According to the research Asmaiyar (2004) women are more conscientious consumers read food packaging labels before deciding to purchase a consumer packaged foods than men. High level of education is also a contributing factor consumers to be more careful in choosing packaged foods. The purpose ofthis research was to determine the selection of food packaging based practice knowledge level, gender, and age of consumer visitors Supermarket ADA Setiabudi Semarang. The type of the research is Explanatory, it’s mean to explain the relations between one variabel and the other or how one variable affects the other variable. The method used was a survey by questionnaire. The approach of study is crossectional and the research population is an affordable all visitors Supermarket ADA Setiabudi Semarang who buy packaged foodproducts. The sample of this study is taken using a quota sampling method, with the number of samples were 68 samples, consisted of 34 men and 34 women. The age of samples were between 17 to 65 years. The results showed that 82.1% rate of good knowledge, 61.8% female respondents, and 57.6% aged adults are categorized properly in practice the selection of packaged foods. Data analysis using chi square test and Pearson correlation. There was a relationship betweenthe level of knowledge with practice selection of food packaging as well as gender and age is a risk factor in the selection of food packaging practices.